Streptococcus suis meningitis in China: a case report - Liu, Tiantian; Liu, Hengfang; Jia, Yanjie (Frontiers in Public Health, 2024)
Introduction: Streptococcus suis is one of the porcine pathogens that have recently emerged as pathogen that is capable of causing zoonoses in some humans. Patients infected with S. suis can present with sepsis, meningitis, or arthritis. Compared to common pathogens such as Meningococcus, Streptococcus pneumoniae, and Haemophilus influenzae, human S. suis infections have been reported only rarely. Methods: This case report described a 57-year-old man who presented with impaired consciousness and fever following several days of backache. He was a butcher who worked in an abattoir and had wounded his hands two weeks prior. The patient was dependent on alcohol for almost 40 years. S. suis was detected in the cerebrospinal fluid by metagenomic next-generation sequencing. Although he received adequate meropenem and low-dose steroid therapy, the patient suffered from bilateral sudden deafness after five days of the infection. The final diagnosis was S. suis meningitis and sepsis. Results: The patient survived with hearing loss in both ears and dizziness at the 60-day follow-up. Discussion: We reported a case of S. suis infection manifested as purulent meningitis and sepsis. Based on literature published worldwide, human S. suis meningitis shows an acute onset and rapid progression in the nervous system. Similar to bacterial meningitis, effective antibiotics, and low-dose steroids play important roles in the treatment of human S. suis meningitis.